FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELUARAN MAKANAN, PENDIDIKAN, DAN KESEHATAN RUMAH TANGGA INDONESIA (ANALISIS DATA SUSENAS 2011) - Ratna Dewi Wuryandari (Research Centre for Population, Indonesian Institute of Sciences, 2015)
The objective of this study is to analyze the effect of socio-demographic and socio-economic variables and location of residence on household expenditures for food, education, and health. Regression analysis shows that household life cycle stages, household size and residential areas have consistent effect on the proportion of food expenditure, education expenditure and health expenditure. Larger household size increases proportion of food expenditure, education expenditure and health expenditure. Stages child household and third generation household have the highest influence on education expenditure and health expenditure. Meanwhile, urban household has the largest impact on the proportion of food expenditure, education expenditure and health expenditure.Â It is also found that households with the highest proportion of food expenditure and with the smallest expenditures on education and health are the ones who have heads of household who are working as free labors or family workers.